Determination of Some Mechanical wood Properties of (Pinus brutia Ten.) and (Cupressus sempervirens L.) Used in Local wood industries . - صالح, أمين (Submission and Review of Research -Biological Sciences Series, 2025)
The aim of this research is to study some mechanical wood properties of (Pinus brutia Ten.) and (Cupressus sempervirens L.) related to their uses in local factories for traditional and structural industries, as well as furniture manufacturing. Wood samples were taken from a local wood mill in Latakkia. The results indicated that Pinus brutia wood is considered as a good quality wood(timber) with a wide range of applications, being classified among the medium-resistant woods to axial compressive (46.15N/mm²) and medium-resistant to static bending (74.81N/mm²). Cupressus sempervirens wood is also regarded as good quality in the field of pallets, furniture production, and traditional industries. classified as a low-resistant wood for axial compressive(35.71 N/mm²)and medium-resistant for static bending (69.05N/mm²). The results showed that Pinus brutia wood has a medium-hardness, while Cupressus sempervirens wood is classified as hard wood based on the indicators of static and specialized properties. Both species were found to have low bending and cohesion according to the bending and cohesion indicators. A significant correlation (p<0.05) was observed between 15% density and both compression resistance and static bending resistance at 15% density for both species. Analysis of mechanical property interrelationships showed significant species-dependent variation in correlation patterns and significance levels.